CT scanning in blunt chest trauma: validation of decision instruments - REICHARDT,GABRIEL SEBBEN (2020)
ABSTRACT Objective: to perform an external validation of two clinical decision instruments (DIs) - Chest CT-All and Chest CT-Major - in a cohort of patients with blunt chest trauma undergoing chest CT scanning at a trauma referral center, and determine if these DIs are safe options for selective ordering of chest CT scans in patients with blunt chest trauma admitted to emergency units. Methods: cross-sectional study of patients with blunt chest trauma undergoing chest CT scanning over a period of 11 months. Chest CT reports were cross-checked with the patients’ electronic medical record data. The sensitivity and specificity of both instruments were calculated. Results: the study included 764 patients. The Chest CT-All DI showed 100% sensitivity for all injuries and specificity values of 33.6% for injuries of major clinical significance and 40.4% for any lesion. The Chest CT-Major DI had sensitivity of 100% for injuries of major clinical significance, which decreased to 98.6% for any lesions, and specificity values of 37.4% for injuries of major clinical significance and 44.6% for all lesions. Conclusion: both clinical DIs validated in this study showed adequate sensitivity to detect chest injuries on CT and can be safely used to forego chest CT evaluation in patients without any of the criteria that define each DI. Had the Chest CT-All and Chest CT-Major DIs been applied in this cohort, the number of CT scans performed would have decreased by 23.1% and 24.6%, respectively, resulting in cost reduction and avoiding unnecessary radiation exposure.